Cultural spillovers from multinationalto domestic firms: Evidence on female employment in Costa Rica - Ricardo Monge-González; Luis Rivera; Nanno Mulder (Transnational Corporations, 2021)
We study cultural spillovers from multinational corporations (MNCs) to domestic companies in the information technology (IT) sector of Costa Rica. Using firm-level panel data for 2001–2011, we explore to what extent domestic firms’ female labour share increases as a result of business operations of MNCs. We find evidence of two channels for cultural spillovers from foreign direct investment (FDI) to domestic IT firms influencing higher shares of female employment: learning (imitation) effects through labour mobility, which allows former MNC employees working in domestic firms to apply skills and gender practices from their previous work experience, and demonstration effects with the presence of MNCs (through competition in the labour market), which include imitation of social norms and values of MNCs by local firms. No evidence was found for a relationship between backward linkages (purchases) of MNCs from domestic suppliers and female labour share. To promote greater participation by women in labour markets through FDI attraction, strengthening cultural spillovers would require implementing FDI promotion policies to (i) enhance the absorptive capacity of domestic IT firms, (ii) attract IT MNCs with greater potential to generate spillovers, and (iii) foster a favourable national investment climate for enhancing business interactions between IT MNCs and domestic IT firms.